Fate of oxygenated intermediates in solar irradiated diluted bitumen mixed with saltwater. (December 2017) - Yang, Zeyu; Zhang, Gong; Hollebone, Bruce P.; Brown, Carl E.; Yang, Chun; Lambert, Patrick; Wang, Zhendi; Landriault, Mike; Shah, Keval
Abstract: Two types of diluted bitumen (dilbit) and a light crude oil spiked onto the surface of saltwater were irradiated with natural solar light in Ottawa to assess the impact of sunlight to the fate of oxygenated intermediates. Oxygenated components, including carbonyl polycyclic aromatic hydrocarbons (PAHs) and acidic polar fractions (naphthenic acid fraction compounds, NAFCs), were identified after periods of solar exposure under both winter and summer conditions. Carbonyl PAHs and NAFCs were formed in both seasons; however, light crude and summer irradiation produced higher abundance of them than dilbits and winter exposure. The formed NAFCs were abundant with the congeners containing a heteroatom of oxygen only ( O o species), accompanied by the minor amounts of sulfur- and nitrogen-containing acids. The produced O o species were predominant with the congeners with light molecular weight, high degree of saturation and heavy oxygen numbers. For both carbonyl PAHs and NAFCs, their abundance continually increased throughout the period of winter exposure. In the summer, some carbonyl PAHs and all O o species increased during the early exposure period; then they decreased with continued exposure for most oils, illustrating their transitional nature. Oxygenated intermediates thus appear to have been created through the photo-oxidation of non-to medium-polar petroleum hydrocarbons or the intermediates of aldehydes or ketones ( O 1 ). Oil properties, the duration of exposure, exposure season and the chemical structure of these intermediates are critical factors controlling their fate through photo-oxidation. The observed chemical changes highlight the effects of sunlight on the potential behavior, fate and impact of spilled oil, with the creation of new resin group compounds and the reduction of aromatics and saturates. These results also imply that the ecological effects of spilled oil, after ageing in sunlight, depend on the specific oil involved and the environmental conditions. Graphical abstract: Highlights: Photo-oxidation formed oxygenated intermediates, especially in summer exposed light oil. O o species were dominant in the formed NAFCs, accompanied by minor S-, N-containing congeners. O o species after solar irradiation shifted to less carbon number, higher degree of saturation and oxygen numbers. The fate of these oxygenated components depends on oil property, exposed time and seasons, and their own chemical structure. Abstract : Oil properties, exposure time, the time of year for solar exposure and the chemical structure of oxygenated intermediates all play critical roles in controlling the fate and behavior of oxygenated intermediates derived through photo-oxidation.